PENGARUH KOMPETENSI DAN DISIPLIN TERHADAP KINERJA GURU SMP NEGERI 1 SEMBAWA BANYUASIN - Amrillah Azrin (Politeknik Negeri Sriwijaya, 2013)
This study have purpose to determine effect of competence, disipline also perfomance of teacher at junior High School number one Sembawa Banyuasin either jointly or individually. Questionnaire instrument competence, discipline, and teacher performance validated with the product moment correlation formula, while the reliability measured by cronbach alpha formula. Data analysis use to correlation and simple regression techniques. There is a positive influence between competence and disipline on the performance of teachers together (partial), where the correlation coefficient = 0.252 RY1.2 at significant level 0.06 and the correlation equation Y = 22,735 + 0.438 X1 + 0.510 X2 + e.There is a possitive influence of competence on the performance of teachers, where the correlation coefficient RY 1 = 0.356 at significant level 0.028 and the correlation equation Y = 56.260 + 0454 X1 + e. There is a positive influence on the performance of teachers between disiplines, where the correlation coefficient RY2=0.366 at sinificant level 0.024 and the correlation equation Y =70,620 + 0.528 X2 +e. It was concluded that the performance teachers can beincrease if competence and disipline increased.